José del Valle: a Benthamite in Central America. (1st January 2014) - Alejandro Gómez,
Abstract : This paper examines the relationship between Jeremy Bentham and José Cecilio del Valle, one of the most important leaders of Central America's independence process. Since this relationship has received little attention from those studying the links between Bentham and Spanish American politicians, with the exception of Miriam Williford 1, we consider that is very important to explore the influence of the utilitarian philosophy in Central America. With this purpose in mind, we will examine the ideas expressed in some of Valle´s writings and government projects throughout his political career dated between 1810 and 1834 in Guatemala.